Type 2 Diabetes and Musculoskeletal Symptoms Among Midlife Women. Issue 5 (October 2019) - Yang, You Lee; Chee, Wonshik; Im, Eun-Ok
Purpose: The purpose of this study was to describe the association between type 2 diabetes and musculoskeletal symptoms among midlife women from 4 major racial/ethnic groups in the United States. Methods: This is a secondary data analysis using the data from 164 participants aged 40 to 60 years of 2 larger survey studies (62 with type 2 diabetes and 102 without type 2 diabetes). In the original studies, the participants completed multiple questionnaires on background characteristics, health status, menopausal status, and musculoskeletal symptoms. The Musculoskeletal Symptom Index for Midlife Women was used to determine the number and severity of musculoskeletal symptoms. For data analysis, independent t tests, Mann-Whitney U tests, and multiple regression analyses were used. Results: The mean number of musculoskeletal symptoms was significantly higher in women with vs without type 2 diabetes as was the mean severity score. In subgroup analyses, among each menopausal stage and non-Hispanic white women, there were significant differences in the numbers and total severity scores between those with type 2 diabetes and without type 2 diabetes. When background characteristics, health status, and menopausal status were controlled, having diagnosis of type 2 diabetes was positively associated with the numbers and total severity scores of musculoskeletal symptoms. Conclusion: Study findings supported significant associations of type 2 diabetes with musculoskeletal symptoms among midlife women. Further studies are recommended to confirm relationships in larger populations.